Pancreatic resections for metastases in the pancreas: analysis of surgical and oncologic outcomes. A retrospective cohort study (Revista Argentina de Cirugía, 2026)
Background: Pancreatic metastases are rare but are likely to be diagnosed more frequently in the future due to the increase in oncology surveillance programs.Objective: The aim of this study was to describe the surgical and oncologic outcomes of a series of patients undergoing surgery for pancreatic metastases.Materials and methods: We conducted a retrospective, descriptive, and multicenter cohort study on patients who underwent pancreatic resections for metastases in the pancreas by the same surgical group between January 2016 and December 2022 in three healthcare providers.Results: A total of 19 patients were operated on, mean age was 59 years, and 11 were women with good performance status and no other evidence of oncologic disease. Clear cell renal cell carcinoma was the primary tumor in 14 cases (7 diagnosed during surveillance), and the remaining primary tumors were one case of breast ductal carcinoma, one testicular cancer, one colorectal cancer, one melanoma and one cervical cancer. The surgical techniques used were pancreatectomies and splenectomies in 7 patients , 4 enucleations (3 conventional procedures and 1 laparoscopic surgery), 3 conventional cephalic pancreaticoduodenectomies, 2 conventional central pancreatectomies and one spleen-preserving distal pancreatectomy. No deaths were reported within 90 days of surgery, and overall survival and disease-free survival were 58 and 53 months, respectively.Conclusion: Resection of pancreatic metastases is safe and provides good oncologic outcomes and overall survival when performed with a multidisciplinary approach in centers with a high volume of hepatobiliary and pancreatic surgeries and in selected cases.
Keywords: pancreatic metastases; pancreatic resection; renal cell carcinoma